Impact of wet-dry cycling on the phase behavior and compartmentalization properties of complex coacervates - Hadi M. Fares (Nature Portfolio, 2020)
Wet-dry cycling is thought to have enabled the production of molecular building blocks of life. Here, the authors investigate the impact of dehydration/rehydration on RNA-containing complex coacervates, which are membraneless compartments formed by phase separation of polyelectrolyte solutions.